DIGITAL CULTURE AS A MODERATING VARIABLE IN THE INFLUENCE OF WORK FACILITIES ON EMPLOYEE PERFORMANCE - Yoga Fortuna Wisnu; Wiwin Saputra; Ifadhila; Desi Ulpa Anggraini; Nabila Cecilia Marasabessy (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to analyze the effect of work facilities on employee performance, with digital culture serving as a moderating variable. In the modern corporate landscape, physical and technological infrastructure must align with the behavioral norms of the workforce to maximize productivity. Using a quantitative approach, data were gathered through structured questionnaires distributed to employees in digital-intensive sectors. Structural Equation Modeling (SEM) was utilized to analyze the direct and interaction effects between variables. The results indicate that comprehensive work facilities significantly enhance employee performance. Furthermore, digital culture acts as a positive and significant moderator, implying that the impact of advanced work facilities on performance is more pronounced in environments with a highly mature digital culture. Organizations must therefore focus not only on procuring physical assets but also on fostering digital mindsets and digital competencies among their human resources.